A painless and flexible bi-directional blood glucose-regulating system inspired by an inverter air conditioner. (3rd August 2022) - Dong, Lina; Ren, Yingzi; Zhang, Wei; Liu, Yu; Liu, Mingzhuo; Hong, Can; Wang, ManYu; Zhan, Bowen; Ding, Xingwei; Wang, Xiaolei
Abstract : A painless, and real-time bi-directional blood glucose regulating drug delivery system was proposed by NIR-defined insulin release and pressure-responsive glucose release. Abstract : Pursuing painless and flexible blood glucose regulation has been a century-long arduous mission. The current therapeutic systems can only regulate blood glucose unidirectionally (reduce), and the adjustment range is large, which is prone to the risk of hypoglycemia. Herein, inspired by the temperature fluctuation range controlled by the inverter air conditioner, we report a new bi-directional blood glucose-regulating drug delivery system (BDRS) consisting of glucose-loaded pressure-responsive nano-vesicles (Glu@PRNV), insulin-loaded black phosphorus nanosheets (Insulin@BPNs), hydrogel, and a painless blood sugar monitor patch. At first, BDRS could monitor blood glucose in real-time through visible color changes. Afterward, according to different requirements, BDRS could release glucose with the guidance of external pressure, or supplement insulin under near-infrared (NIR) irradiation, through which, the blood glucose level of diabetics could be accurately accommodated within a reasonable fluctuation range, thus minifying the likelihood of sudden hyperglycemia or hypoglycemia. Collectively, the supply–demand balance of blood glucose could be maintained via this real-time bi-directional drug delivery system, thereby improving the quality of life of diabetics. We have also verified the universality of this technique through a similar bi-directional sleep regulation.